Peripheral Inflammation Regulates CNS Immune Surveillance Through the Recruitment of Inflammatory Monocytes Upon Systemic α-Synuclein Administration - Peralta Ramos, Javier María; Iribarren, Pablo; Bousset, Luc; Melki, Ronald; Baekelandt, Veerle; Van der Perren, Anke (Frontiers in Immunology, 2019)
Innate immune activation and chronic neuroinflammation are characteristic features of many neurodegenerative diseases including Parkinson’s disease (PD) and may contribute to the pathophysiology of the disease. The discovery of misfolded alpha-synuclein (αSYN) protein aggregates, which amplify in a “prion-like” fashion, has led us to consider that pathogenic αSYN might be hijacking the activation and mobilisation mechanism of the peripheral immune system to reach and disseminate within the CNS. Furthermore, our lab and other groups have recently shown that αSYN can adopt distinct fibril conformations or “strains” with varying levels of pathogenic impact. Therefore, the aim of this study was to assess the impact of peripheral inflammation on αSYN spreading in order to better understand the participation of the immune system in the progression of PD. The results presented here show that intraperitoneal LPS injection prior to systemic intravenous recombinant administration of two different αSYN pathogenic strains (fibrils or ribbons) in wild type mice, induces an increase in brain resident microglia and promotes the recruitment of leukocytes towards the brain and the spinal cord. Our findings show for the first time that αSYN can be internalised by LPS-primed inflammatory monocytes, which in turn favours the dissemination from the periphery towards the brain and spinal cord. Further, we found a differential recruitment of CD4+ and CD8+ T cells after LPS priming and subsequent administration of the αSYN ribbons strain. Together, these data argue for a role of the peripheral immune system in αSYN pathology.